'Links2HealthierBubs' cohort study: protocol for a record linkage study on the safety, uptake and effectiveness of influenza and pertussis vaccines among pregnant Australian women. Issue 6 (20th June 2019) - Sarna, Mohinder; Andrews, Ross; Moore, Hannah; Binks, Michael J; McHugh, Lisa; Pereira, Gavin F; Blyth, Christopher C; Van Buynder, Paul; Lust, Karin; Effler, Paul; Lambert, Stephen B; Omer, Saad B; et al.
Abstract : Introduction: Pregnant women and infants are at risk of severe influenza and pertussis infection. Inactivated influenza vaccine (IIV) and diphtheria-tetanus-acellular pertussis vaccine (dTpa) are recommended during pregnancy to protect both mothers and infants. In Australia, uptake is not routinely monitored but coverage appears sub-optimal. Evidence on the safety of combined antenatal IIV and dTpa is fragmented or deficient, and there remain knowledge gaps of population-level vaccine effectiveness. We aim to establish a large, population-based, multi-jurisdictional cohort of mother-infant pairs to measure the uptake, safety and effectiveness of antenatal IIV and dTpa vaccines in three Australian jurisdictions. This is a first step toward assessing the impact of antenatal vaccination programmes in Australia, which can then inform government policy with respect to future strategies in national vaccination programmes. Methods and analysis: 'Links2HealthierBubs' is an observational, population-based, retrospective cohort study established through probabilistic record linkage of administrative health data. The cohort includes births between 2012 and 2017 ( 607 605 mother-infant pairs) in jurisdictions with population-level antenatal vaccination and health outcome data (Western Australia, Queensland and the Northern Territory). Perinatal data will be the reference frame to identify the cohort. Jurisdictional vaccination registers will identify antenatal vaccination status and the gestational timing of vaccination. Information on maternal, fetal and child health outcomes will be obtained from hospitalisation and emergency department records, notifiable diseases databases, developmental anomalies databases, birth and mortality registers. Ethics and dissemination: Ethical approval was obtained from the Western Australian Department of Health, Curtin University, the Menzies School of Health Research, the Royal Brisbane and Women's Hospital, and the West Australian Aboriginal Health Ethics Committees. Research findings will be disseminated in peer-reviewed journals, at scientific meetings, and may be incorporated into communication materials for public health agencies and the public.